Joint erosion in rheumatoid arthritis: interactions between tumour necrosis factor α, interleukin 1, and receptor activator of nuclear factor κB ligand (RANKL) regulate osteoclasts. Issue 4 (12th March 2004) - O' Gradaigh, D; Ireland, D; Bord, S; Compston, J E
Abstract : Background: Osteoclasts, specialised bone resorbing cells regulated by RANKL and M-CSF, are implicated in rheumatoid joint erosion. Lymphocyte-monocyte interactions activate bone resorption, this being attributed to tumour necrosis factor α (TNFα) and interleukin 1 β (IL1β) enhanced osteoblast expression of RANKL. In animal studies, TNF potently increases osteoclast formation in the presence of RANKL. RANKL-independent osteoclastogenesis also occurs, though IL1 is required for resorptive function in most studies. These inflammatory cytokines have a pivotal role in rheumatoid arthritis, Objective: To study the interactions of TNFα and IL1β with RANKL, particularly the time course of the interactions and the role of lymphocytes. Method: Cultures of lymphocytes and monocytes (osteoclast precursors) or of purified CD14 + cells alone (osteoclast precursors) were exposed to various combinations of TNFα, RANKL, and IL1β or the inhibitors osteoprotegerin, IL1 receptor antagonist, or neutralising antibodies to RANKL or to IL1. Osteoclastogenesis and resorptive activity were assessed on microscopy of dentine slices. Results: TNFα potently increased osteoclast proliferation/differentiation in the presence of RANKL. This effect was greatest when RANKL was present before but not after exposure of osteoclast precursor cells to TNFα. The resorptive activity of osteoclasts generated by TNFα in the absence of RANKL was critically dependent upon IL1, which was expressed by lymphocyte-monocyte interaction. Conclusion: TNFα potently enhances RANKL mediated osteoclast activity. Interactions between TNFα and IL1 also result in osteoclastic activity independently of RANKL. These findings will inform therapeutic approaches to the prevention of joint erosion in rheumatoid arthritis.